VIABILITAS SPERMATOZOA PETAURUS BREVICEPS PAPUANUS T. - SUARNI, NI MADE RAI; ERMAYANTI, I GUSTI AYU MANIK (2009)
Keywords: Petaurus berviceps papuanus T.; spermatozoa; viability

(untitled) (Jurnal Biologi Udayana, 2009)
Experiment to determine the spermatozoa viability of Petaurus berviceps papuanus T. has been performed. Observation was done under microscope and trypan blue was used as stain. Viable spermatozoa were counted from a total of 100 spermatozoa. It was found that 4,75 % of the spermazoa could be maintained for 7.5 hours in the DMEM (Dulbecco's modified Eagle's medium) at 35oC.